The structure and algorithm interaction kardiodiahnostychnoyi system in the complex systems, intelligent buildings - Кульчицька, Т.І.; Щербак, Л.М. (Proceedings of National Aviation University, 2008)
Substantiation of structure and algorithm of co-operation of automatic cardiology diagnostic system in the complex of systems of an intelligent building were considered.